Novel turboshaft engines design and optimisation for rotorcraft applications. - Ortiz-Carretero, Jesus (Cranfield University, 2018)
Since the inception of the first gas turbine engines, scientists and aircraft propulsion designers have attempted to improve engine efficiency, size, weight, fuel consumption and power output. In the current scenario, where the conventional gas turbine technology has almost reached its maturity, companies and researchers are starting to seek new engine architectures and novel cycles to comply with the next future aviation challenges. One of the proposed solutions is the implementation of an auxiliary combustion process into the turbines, known as reheated cycle. In the reheated cycle, the gas from an expansion process (through a turbine stage or a whole turbine) is burned before the next expansion. This concept has the potential to increase the specific work, at the same time the thermal efficiency is improved. Numerous investigations have been performed on the application of the reheated cycle to turbojet and civil turbofan engines. However, no studies are published about the potential application of this technology in rotorcraft powerplants. Therefore, the aim of this research project is to accomplish an exhaustive analysis and optimisation of a reheated turboshaft engine in terms of thermal efficiency and engine weight. The optimal engines identified at this stage are to be evaluated at mission level in order to assess the final impact on mission fuel abatement. For this matter, models for the performance simulation of a representative helicopter and for the thermodynamic analysis of the engine architectures have been developed and validated against experimental data. An additional module estimating the cooling flows fluctuation with the engine cycle parameters has been coupled with the engine performance model. Finally, a procedure for the sizing of reheated turboshaft engines have been developed and validated by the author. The different models have been built after a reference Twin-Engine Medium (T EM) helicopter, the Sikorsky UH-60A Black Hawk helicopter powered by two General Electric T700-GE-700 turboshaft engines. The aforementioned models have been integrated in a common simulation framework for the completion of a preliminary parametric analysis showing the sensitivity of the reheated configurations to changes in the engine design variables. In particular, three distinct reheated architectures have been investigated together with a conventional engine for comparison purposes. The individual response of each engine architecture has been discussed. The deployed framework has been then coupled with a Genetic Algorithm optimiser to efficiently seek for the best candidate engines in terms of total weight and Specific Fuel Consumption at cruise (SFCcr). At this step, Response Surface Models (RSMs) have been developed for the fast estimation of engine weight and coupled with the optimiser routine. It has been proven that the reheated engines have the potential to reduce engine mass and increase thermal efficiency in comparison with the baseline engine, although the optimal conventional engine still shows superior performance under the conditions simulated. This conclusion has been also confirmed by the results obtained at mission level. A final mission level multi-objective optimisation has been conducted for the conventional engine targeting the minimisation of the overall mission fuel burn and NOᵪ emissions. A representative model for the prediction of the combustor emissions production has been developed and validated for this purpose. The trade-off existing between fuel efficiency and pollutant depletion has been highlighted along with the potential benefits in block fuel and NOᵪ inventory.
Keywords: reheated cycle; auxiliary combustion; rotorcraft; turboshaft; NOᵪ; fuel efficiency; pollutant depletion